1992
DOI: 10.1016/0022-328x(92)88002-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyfunctional diorganomercurials and their transmetallation to diorganozincs. Applications to the preparation of optically active secon

Abstract: Two new methods of preparation of functionalized diorganomercurials have been developed. The first method involves a substitution reaction of (ICH,),Hg with zinc-copper reagents FG-RCu(CN)ZnI in THF/DMF at-60°C. Functional groups such as an ester, nitrile, ketone, phosphonate, halide, and boronic ester are tolerated in this reaction. The second method involves a reductive transmetallation between poly-functional organozinc halides and mercurous chloride (Hg,CI,). This very convenient procedure provides a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 85 publications
(4 reference statements)
1
11
0
Order By: Relevance
“…Phenol 3 , aniline 10 , and cinnamaldehyde ( 17 ) were obtained commercially. Aniline derivative 11 and chiral secondary alcohols 18 , 19 , 20 , 21 , 22 , 23 , 25 , and 26 17 are all known compounds, and the spectral data, optical data, and analytical data of these compounds which we obtained agreed with those in the literature.…”
Section: Methodssupporting
confidence: 84%
“…Phenol 3 , aniline 10 , and cinnamaldehyde ( 17 ) were obtained commercially. Aniline derivative 11 and chiral secondary alcohols 18 , 19 , 20 , 21 , 22 , 23 , 25 , and 26 17 are all known compounds, and the spectral data, optical data, and analytical data of these compounds which we obtained agreed with those in the literature.…”
Section: Methodssupporting
confidence: 84%
“…Hanke has demonstrated that the reaction of mercury(II) acetate with neat phenyl halides at 140°C yields (para-halophenyl)mercuric acetate complexes [13], whereas Rausch and co-workers mercurated ferrocene in glacial acetic acid using mercury(II) acetate [14]. Even more relevant is a Hg-C bond formation observed when mercury(II) acetate is treated with a vinylboronate; the observed product is a bis(vinylated)-mercury(II) complex [15]. Also, as mentioned in the Introduction, Challenger and Richards reported that the reaction of mercuric oxide and arylboronic acids yields diarylmercurials [12], but the products were only characterized by melting point and in one case, elemental analysis.…”
Section: Synthesismentioning
confidence: 89%
“…29 The zinc insertion shows a remarkable functional group tolerance and most common organic functional groups (i.e. ester,29,35-52 ketone,29,35 cyanide,29,35-43,47,49-52,54 halide, 29,35,43,48,50,52 iV^V-bis(trimethylsilyl)amino group,55 primary and secondary amino groups,56 amide and phthalimide,25,56,57 trialkoxysilyl group,58 sulfoxide,59 sulfide,59 sulfone,59,60 thioester,60 boronic ester,46,48,50 enone,40,53 and phosphate39,61) can be present during the organozinc formation (eq 5). Only hydroxyl groups (deprotonation) or nitro and azide functionalities (inhibition of the zinc insertion) cannot be present in the alkyl iodide.…”
Section: Metalmentioning
confidence: 99%